Managing uncertainties in fatigue damage prognosis using piezoelectric transducers - Hu, Shan. (2013)
Damage Prognosis is estimating the systems remaining lifespan by measuring the current state of the system, estimating the future loading environment for the system, and predicting through simulation. An accurate Prognosis could help to predict the structural failure before it take place, hence to prevent unwanted losses of structure and human lives.